The Urgency of the Improved Intensity of Traffic Usage Safety Education by Students - Subaryata, Subaryata; Mutharuddin, Mutharuddin; Irawati, N; Nugroho, S; Bowo, L P; Rustandi, A; Mardiana, T S; Fitri, H A; Kurnia, S H M; Puriningsih, F S; et al. (RSF Conference Series: Engineering and Technology, 2022)
Motorcycle is the most commonly owned transportation mode by most Indonesian citizens due to its affordable price and size, which makes them suitable for road shapes in Indonesian residential area. In recent times, student motorcyclists have increased in number, although using motorcycles by people younger than 17 years old violates the Law of Traffic Usage and Road Transportation and might be penalized. Motorcycles are the type of vehicle that has accident-prone characteristics. Many student motorcyclists have been in traffic accidents resulting in injuries, physical disabilities even deaths. Traffic usage safety has been conducted in various types of media, written or electronic. It has been done in school counseling as well. Most students have yet to take the session regularly. The material and methods of education delivery of traffic have been rated well. The primary data is obtained by sharing questionnaires using Google Forms by junior and senior high school students in Bekasi Regency. The data analysis uses Crosstab and Chi-Square tests. Based on the analysis result, there is a connection between gender, age, school level, traveling time, and traffic usage education intensity with traffic accidents that have been experienced. The more intense the education/socialization on traffic safety, the less the percentage of an accident will be. Theoretically, student motorcyclists’ understanding of traffic safety is rated well, although the application consistency has yet to be seen. Therefore, there has to be an improvement in the education/ socialization intensity of traffic that enables every student to receive the educational material.